Pasar Modal Syariah sebagai Pilar Pendukung Pertumbuhan Industri Halal: Sebuah Tinjauan Komprehensif - Batubara, Maryam; Nasution, Inayatul Widad (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The Sharia Capital Market and Halal Industry play an integral role in establishing a financial ecosystem that adheres to Islamic financial principles and supports the growth of industrial sectors that meet halal standards. This research aims to provide a comprehensive review regarding the contribution of the Sharia Capital Market as the main pillar supporting the growth of the halal industry. Through a literature review and document analysis approach, this research identifies that the Sharia Capital Market not only acts as an alternative source of financing, but also shapes the financial environment in accordance with Islamic principles. Islamic investment instruments, such as sukuk and Islamic shares, play a key role in providing ethical financing alternatives. Regulatory factors, investor participation, and the level of public trust are identified as crucial elements that influence the integration of the Sharia Capital Market with the halal industry. These findings provide a basis for stakeholders to develop a financial ecosystem that supports economic growth in accordance with the principles of Islamic finance and sustainability.